Book review: Reddy, Groundwater Governance: Development, Degradation and Management. (July 2019) - Bassi, Nitin
Reddy, Groundwater Governance: Development, Degradation and Management (First Edition). Delhi and Jaipur: Rawat Publications, 2016, 216 pp., ₹695 (hardcover). ISBN: 978-8131607664.